Waste management: a study on generating organic fertilizer from oil and grease trap systems - Rojas-Vargas, Julián (2022)
The grease and oil trap systems (GOTS) of four university food service establishments (FSE) were assessed and treated to evaluate the potential use of the sludge collected to produce compost. The sludge collected from each FSE was kept in a drying bed for 30 days (SDB), during which time calcium oxide was frequently added for stabilization. The sludge deposited monthly was reduced to half after the drying process and was then deposited in a composter and mixed for a period of 22 days with constant agitation. The compost obtained was treated with degrading enzymes and was denominated enzymatic composting (EC), while the remaining compost was not treated with enzyme and was denominated non-enzymatic compost (NEC). The total composting cycle of the sludge lasted 83 days, during which time various physical and chemical analyzes were conducted in the three types of substrates (SDB, NEC, and EC). The total time of the research was 2.5 years. The percentages of phosphorus, potassium, magnesium, and calcium suggest the use of the three substrates as organic fertilizer. A recommendation resulting from this research is to evaluate the sludge quality by mixing it with other substrates such as fruit peels with high nitrogen content and the sludge from wastewater treatment systems.